Distribution. Temperate to subarctic waters of the N Atlantic including S Davis Strait, Gulf of Saint Lawrence, Barents Sea, and North Sea, S to Cape Cod (USA) in the E and the coasts of N France in the W. Extralimital sightings in the Baltic Sea, Bay of Biscay, and Iberian Peninsula. in Delphinidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Distribution. Temperate to subarctic waters of the N Atlantic including S Davis Strait, Gulf of Saint Lawrence, Barents Sea, and North Sea, S to Cape Cod (USA) in the E and the coasts of N France in the W. Extralimital sightings in the Baltic Sea, Bay of Biscay, and Iberian Peninsula. Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Delphinidae, pp. 410-526 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 489, DOI: 10.5281/zenodo.6610922